7, 13, 19 and 25 have a common difference: 6.
6 added to 7 gives us 13; 6 added to 13 gives us 19, and so on.
Explicit formula: a(n) = 7 + 6(n-1), where 7 is the first term and n is the counter (1, 2, 3, ...).
The first term is 7 (given). This corresponds to n=1.
The second term is a(2) = 7 + 6(2-1), or 7 + 6, or 13. This corresponds to n = 2.
and so on.
Answer:
<h2>x³ + x² - 3x - 3</h2>
Step-by-step explanation:
I'm assuming g*f means g times f, so you want to multiply the two functions together.
(x² - 3)(x + 1) Since the product is 2 binomials, use FOIL
= x²(x) + x²(1) - 3(x) - 3(1)
which simplifies to
<h2>x³ + x² - 3x - 3</h2>
Answer:
the answer is 22 hope this helps
Step-by-step explanation:
7(-7)= -49
-49+149=100
100-56=44
44/2=22
Answer:
3.13
Step-by-step explanation:
2.1^-1.4^2 = 2.45
Square root 2.45 + 1.56
1.56 x 2= 3.13
Answer:
f(-2) = 44
Step-by-step explanation:
Hello there! Lets get started solving this function!
For a function, whenever we see f(x) = ... , the function is simply asking the value of the equation at x! So, if replace f(x) with f(-2), we simply substitute x with -2 in the equation! Lets get started!
![f(x) = -7x + 5x^{2} + 10\\f(-2) = -7(-2) + 5(-2)^{2} + 10\\f(-2) = 14 + 20 + 10\\f(-2) = 44\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-7x%20%2B%205x%5E%7B2%7D%20%2B%2010%5C%5Cf%28-2%29%20%3D%20-7%28-2%29%20%2B%205%28-2%29%5E%7B2%7D%20%2B%2010%5C%5Cf%28-2%29%20%3D%2014%20%2B%2020%20%2B%2010%5C%5Cf%28-2%29%20%3D%2044%5C%5C)
First, we can write the original function. Next, we substitute in -2 for x. Then, we find our final terms. Finally, we are given that f(-2) = 44.
Hope this helps! Remember, math is fun!